The use of songs to enhance the learning of english vocabulary among year five pupils of Sekolah Kebangsaan Segong Bau / Doreh Nasei - Nasei, Doreh (2007)
The use of songs in teaching vocabulary is not a new thing in school. It has been used by the teacher as one of the teaching method in the classroom teaching. The use of songs can enhance and motivate the students to participate actively in the classroom teaching and learning process. The main aim of this study is to find out whether the use of songs to teach vocabulary among 26 Year Five pupils of Sekolah Kebangsaan Segong Bau would bring obvious differences in performance of the pupils. After a month conducted, [ July 3,2006 until August 3, 2006 ] the pupils who were administered during the treatment achieved significantly progress in their language and they managed to overcome the passiveness. With songs the pupiis interact with their peers actively. These findings bring to the extend that songs actually enhanced the pupils motivation and preference toward the used of songs in the classroom. It was concluded that the used of songs for the teaching of vocabulary in English language classroom were very effective and successful in improving pupils interacting mode.